Filtration Capacity and Behaviour of Juvenile Green-Lipped Mussels in Small-Volume Bioassays - Sanjayasari, Dyahruri; Gali, Sucharita (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2025)
This research specifically observes the duration of valve opening and closure in three different size classes of juvenile mussels (Perna canaliculus) over a 60-minute period after exposure to the microalgae Isochrysis galbana. Current study would like to understand this behaviour as a precursor to using flow cytometry (FCM) to accurately measure the juvenile mussels' filtering capabilities under the FCM set up. There is still limited information on the use of experimental set up of flowcytometry on measuring the filtration of the juvenile mussels. Two factors used in the experimental set up; i.e. the size class of juvenile mussels, and the observation time (T1- T60). The results indicated that both mussel size and observation time significantly influence the proportion of time valves remain fully open, with juvenile mussels generally exhibiting different behaviour patterns (such as more crawling). Current study also measure the clearance of the microalgae, which shown the larger size class of mussels exhibit higher cells clearance compared to the smaller size of mussels. Ultimately, the study concludes that while valve observation indicates filtering, further refined methods are needed to ensure FCM accurately measures the actual particle removal capability. Keywords: Juvenile mussel, valve opening, valve closure, filtering behaviour, flow cytometry.